CORRELATION OF NEUTROPHIL LYMPHOCYTE RATIO WITH HbA1C IN DIABETIC ULCERS - Ni Nengah Dwi Putri Meili Wahyuni; Ersandhi Resnhaleksmana; Fihiruddin Fihiruddin (Meditory : The Journal of Medical Laboratory, 2026)
Background: Patients diagnosed with diabetes are susceptible to complications, including diabetic ulcers. HbA1C is one of the key parameters used to evaluate glycemic control At the same time, the neutrophil-to-lymphocyte ratio (NLR) is a test used to detect inflammatory processes in patients with diabetes mellitus who develop diabetic ulcers. Objective: This research analyzes the relationship between the neutrophil-to-lymphocyte ratio (NLR) and HbA1C levels in patients with diabetes mellitus and diabetic foot ulcers. Methods: The research has a cross-sectional design. Data were collected retrospectively using non-probability sampling through a purposive sampling method from January 2024 to January 2025. Data were obtained from 83 individuals diagnosed with diabetes mellitus, including those with diabetic ulcer. Results: The highest NLR value was 26.47 and the lowest was 1.14. The highest HbA1C value was 51.0, while the lowest was 5.40. Spearman's statistical test indicated no significant correlation between NLR and HbA1C in patients with diabetes mellitus and diabetic foot ulcers (p = 0.534 > 0.05). Conclusions: There is no correlation between the neutrophil-to-lymphocyte ratio (NLR) and HbA1C levels in patients with diabetes mellitus and diabetic foot ulcers.